Lower limb muscle injury location shift from posterior lower leg to hamstring muscles with increasing discipline-related running velocity in international athletics championships - Edouard, P.; Hollander, K.; Navarro, L.; Lacourpaille, L.; Morales-Artacho, A. J.; Hanon, C.; Morin, J.-B.; Le Garrec, S.; Branco, P.; Junge, A.; Guilhem, G. (Journal of Science and Medicine in Sport, 2021)
Objective: To analyse the rates of lower limb muscle injuries in athletics disciplines requiring different running velocities during international athletics championships. Design: Prospective total population study. Methods: During 13 international athletics championships (2009-2019) national medical teams and local organizing committee physicians daily reported all newly incurred injuries using the same study design, injury definition and data collection procedures. In-competition lower limb muscle injuries of athletes participating in disciplines involving running (i.e. sprints, hurdles, jumps, combined events, middle distances, long distances, and marathon) were analysed. Results: Among the 12,233 registered athletes, 344 in-competition lower limb muscle injuries were reported (36% of all in-competition injuries). The proportion, incidence rates and injury burden of lower limb muscles injuries differed between disciplines for female and male athletes. The most frequently injured muscle group was hamstring in sprints, hurdles, jumps, combined events and male middle distances runners (43-75%), and posterior lower leg in female middle distances, male long distances, and female marathon runners (44-60%). Hamstring muscles injuries led to the highest burden in all disciplines, except for female middle distance and marathon and male long distance runners. Hamstring muscles injury burden was generally higher in disciplines requiring higher running velocities, and posterior lower leg muscle injuries higher in disciplines requiring lower running velocities. Conclusions: The present study shows discipline-specific injury location in competition context. Our findings suggest that the running velocity could be one of the factors that play a role in the occurrence/location of muscle injuries.